49.2k views
1 vote
Hello hope all is well with you can you help me with this please number 2

Hello hope all is well with you can you help me with this please number 2-example-1

1 Answer

2 votes

Our equation is:


4(-x)-2(-x)+2=9+(-x)

Then we can operate it in the following way, I'll do it step by step


\Rightarrow4(-x)-2(-x)=(4-2)(-x)=2(-x)
\begin{gathered} \Rightarrow2(-x)+2=9+(-x) \\ \Rightarrow2(-x)+2-2=9+(-x)-2 \\ \Rightarrow2(-x)=7+(-x) \end{gathered}
\begin{gathered} \Rightarrow2(-x)-(-x)=7+(-x)-(-x) \\ \Rightarrow(2-1)(-x)=7+(1-1)(-x)=7 \\ \Rightarrow1(-x)=7 \\ \Rightarrow-x=7 \end{gathered}

And, if -x=7, then


\begin{gathered} 4(7)-2(7)+2=9+(7) \\ \Rightarrow28-14+2=9+7 \\ \Rightarrow16=16 \end{gathered}

User BurpmanJunior
by
5.2k points